Epipelon responses to N and P enrichment and the relationships with phytoplankton and zooplankton in a mesotrophic reservoir - Tavares, Diego Alberto; Lambrecht, Richard Wilander; de Almeida Castilho, Maria Carolina [UNESP]; Henry, Raoul [UNESP]; Ferragut, Carla (Springer Nature, 2019)
The phototrophic epipelon has been suggested to play an important role in ecosystems, especially those with shallow depths; however, only a few studies have investigated this function. Nutrient availability has been shown to be a determining factor for autotrophic interactions and can potentially interfere with the food web, as eutrophication. Thus, we evaluated the responses of epipelon, phytoplankton and zooplankton to combined and isolated N and P addition, during the enrichment period (14 days) and after 12 days with no enrichment. It was hypothesized that P addition (the limiting nutrient) should decrease the photosynthetic potential of the epipelon, due to the rapid increase in phytoplankton and zooplankton biomass, which can strongly attenuate light, and that the opposite effect would be observed after a period with no enrichment. We developed an in situ experiment with combined and isolated N and P enrichment at open-bottom mesocosms. The addition of P, individually and combined, augmented phytoplankton chlorophyll-a concentrations during the enrichment period, while zooplankton density only responded positively after day 14. After 12 days with no enrichment, the phytoplankton chlorophyll-a and zooplankton density decreased. While P enrichment had no significant effect on epipelon chlorophyll-a, there was a significant increase in the photosynthetic potential detected 12 days after the enrichment was stopped. In conclusion, the present study demonstrated that P enrichment reduces the photosynthetic potential of epipelon, and that variations in nutrient availability can modulate relationships among phytoplankton, zooplankton and epipelon. Drastic changes in the growth and development of the phototrophic epipelon, due to the input of nutrients, could directly impact the functioning of shallow tropical lakes and reservoirs.
Keywords: Chlorophyll-a concentrations; N and P enrichment; Open-bottomed mesocosms; Zooplankton density